sevara THE IMPACT ON LANGUAGE LEARNING ON CHILD REARING: THE IMPACT ON LANGUAGE LEARNING ON CHILD REARING - Soipova, Sevara (Журнал иностранных языков и лингвистики, 2022)
the current era is called the internet era. Therefore, every baby and child are being able to work with social medias nowadays and they are learning different languages quickly by them. In this article, we will look at the pros and cons of following children ages 2 to 6 to learn a language on their own.